DAMPAK PROFITABILITAS, LIKUIDITAS DAN PENGUNGKAPAN ISLAMIC SOCIAL REPORTING TERHADAP RETURN SAHAM - Fatmawati, Elsaputri Dyahayu; Prasetyoningrum, Ari Kristin; Farida, Dessy Noor (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2020)
Mining companies are capital-intensive industries and have high risks and their business activities have more physical and social environmental impacts compared to other business sectors. The purpose of this study was to analyze the effect of Return On Equity, Current Ratio, and Islamic Social Reporting disclosure to return stock. The samples used in this research are 13 mining companies listed in Indonesia Sharia Stock Index (ISSI) period 2014-2018 that are determined by purposive sampling. This research using the method of multiple linear regression analysis and hypothesis testing using program Eviews 9. The result of this research shows that in partial, Return On Equity and Current Ratio does not have a significant effects to return stock. While Islamic Social Reporting has significant effect to return Stock.